Karankawa - Rocha, Iliana (Pitt poetry series., 2015)
Karankawa is a collection that explores some of the ways in which we (re)construct our personal histories. Rich in family narratives, myths, and creation stories, these are poems that investigate passage--dying, coming out, transforming, being born--as well as the gaps that also reside in our stories, for, as Rocha suggests, the opportunity to create myths is provided by great silences. Much like the Karankawa Indians whose history works in omissions, Karankawa reconfigures such spaces, engaging with the burden and freedom of memory in order to rework and recontextualize private and public mythologies. First and last, these are poems that honor our griefs and desires, for they keep alive the very things we cannot possess.